Evaluating solvothermal and mechanochemical routes towards the metal–organic framework Mg2(m-dobdc). Issue 41 (6th July 2022) - Chen, Elena Y.; Mandel, Ruth M.; Milner, Phillip J.
Abstract : Mechanochemical and solvothermal routes to the metal–organic framework Mg2 ( m -dobdc) bearing coordinatively unsaturated Mg(ii ) sites are presented. The mechanochemical synthesis produces porous material exhibiting higher carbon dioxide uptake. Abstract : Metal–organic frameworks bearing coordinatively unsaturated Mg(ii ) sites are promising materials for gas storage, chemical separations, and drug delivery due to their low molecular weights and lack of toxicity. However, there remains a limited number of such MOFs reported in the literature. Herein, we investigate the gas sorption properties of the understudied framework Mg2 ( m -dobdc) (dobdc 4− = 4, 6-dioxido-1, 3-benzenedicarboxylate) synthesized under both solvothermal and mechanochemical conditions. Both materials are found to be permanently porous, as confirmed by 77 K N2 adsorption measurements. In particular, Mg2 ( m -dobdc) synthesized under mechanochemical conditions using exogenous organic base displays one of the highest capacities reported to date (6.14 mmol g −1 ) for CO2 capture in a porous solid under simulated coal flue gas conditions (150 mbar, 40 °C). As such, mechanochemically synthesized Mg2 ( m -dobdc) represents a promising new framework for applications requiring high gas adsorption capacities in a porous solid.